IDENTIFICATION AND ANTIMICROBIAL RESISTANCE PROFILE OF MICROORGANISMS ISOLATED FROM DIABETIC FOOT ULCERS - Neha Goel; Hina Singh; Sagar Kashyap (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Diabetes increases the susceptibility of wounds to a variety of infections, including bacteria. It is a major factor in lower limb amputations and can progress from a soft tissue infection to a bone infection. For a good prognosis, it's crucial to make an early diagnosis and choose a course of therapy based on the identification of the pathogens and their antimicrobial susceptibility patterns. As a result, the goal of this study was to identify the bacteria that cause foot ulcers and assess their profile of antibiotic resistance.Materials and Methods: Using sterile swabs, samples of diabetic foot ulcers were aseptically taken. Culture, Gram staining, and biochemical tests were used to identify the isolates. The Kirby-Bauer disc diffusion method was used to assess the antibiotic susceptibility of the isolated bacteria.Results: Out of 150 patients with diabetes, 67 patients had diabetic foot ulcer. 37.3% of them were female and 62.7% of them were male. Of these, 55.2% were Gram negative and 41.7% were Gram positive isolates. The most predominant bacteria among the isolated microorganisms were Staphylococcus aureus (31.3%), followed by Pseudomonas species (17.9%). Most of the Gram positive bacteria were resistant to dicloxacillin and Cefuroxime. The majority of Gram negative bacteria were resistant to Cefepime followed by tetracycline, cefotaxim, and cefuroxime.Conclusion: Numerous multidrug resistant bacteria and a wide range of pathogens can infect diabetic foot ulcers. The outcome demonstrated a general rise in bacterial resistance to antimicrobial drugs and highlights the significance of microbiological analysis and antimicrobial susceptibility testing prior to beginning antibiotic treatment for infections in diabetic foot ulcers.